Discussion on International Standards Related to Testing and Evaluation of Lithium Battery Energy Storage - Zhou, Yuan; Wang, Feng; Xin, Tian; Wang, Xin; Liu, Ya; Cong, Lin (Distributed Generation & Alternative Energy Journal, 2021)
With the massive penetration of distributed energy, energy storage has become an indispensable key link. Lithium battery energy storage is one of the most promising technologies in the ﬁeld of energy storage. The discussion and Research on foreign lithium battery energy storage standards can better evaluate them to enter the international market. This article interprets some internationally representative test standards, and compares some key test items in accordance with international standards, aiming to promote domes- tic companies to understand international standards and ultimately produce products that meet international standards. It also points out the reqirements of reusing batteries and factories in the cascade utilization process stipulated by the UL 1974 evaluation standard. This paper provides technical support for the supervision and management of the entire life cycle of lithium batteries and also helps to promote the industry’s circular low-carbon and sustainable development.